Risk factors for severe lower extremity ischemia following venoarterial extracorporeal membrane oxygenation: an analysis using a nationwide inpatient database. Issue 1 (13th April 2022) - Honda, Akira; Michihata, Nobuaki; Iizuka, Yoichi; Uda, Kazuaki; Morita, Kojiro; Mieda, Tokue; Takasawa, Eiji; Ishiwata, Sho; Tajika, Tsuyoshi; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo; et al.
Abstract : Objectives: Venoarterial extracorporeal membrane oxygenation is increasingly being used as a life-saving modality in critically ill patients. Despite its necessity, severe lower extremity ischemia associated with venoarterial extracorporeal membrane oxygenation remains a potentially devastating complication. We aimed to investigate the incidence and risk factors for severe lower extremity ischemia requiring fasciotomy or amputation following venoarterial extracorporeal membrane oxygenation. Methods: All patients who received venoarterial extracorporeal membrane oxygenation during hospitalization were identified in a Japanese national inpatient database from July 1, 2010 to March 31, 2018. The primary outcome was occurrence of severe lower extremity ischemia that required fasciotomy or amputation. We used cause-specific proportional hazard models to examine the associations between potential risk factors and outcomes. We also performed a competing-risk analysis to estimate the cause-specific HR for severe lower extremity ischemia using a multivariable competing-risk Cox proportional hazard model with adjustment for potential risk factors. Results: A total of 29 231 patients who underwent venoarterial extracorporeal membrane oxygenation during hospitalization were identified. Of these, 98 patients (0.3%) had lower extremity ischemia requiring fasciotomy or amputation. The young group (≤18 years) had a significantly higher proportion of severe lower extremity ischemia cases than the adult (19–59 years) and elderly (≥60 years) groups (1.4%, 0.5%, and 0.2%, respectively; p<0.001). In a multivariable competing-risk Cox proportional hazards regression model, younger age (HR 3.06; 95% CI 1.33 to 7.02; p<0.008) and consciousness disturbance on admission (HR 2.53; 95% CI 1.60 to 3.99; p<0.001) were significantly associated with higher likelihood of severe lower extremity ischemia. Conclusion: In this study using a nationwide database, younger age and consciousness disturbance on admission were associated with higher risk of severe lower extremity ischemia following venoarterial extracorporeal membrane oxygenation. Level of evidence: Level Ⅲ—prognostic and epidemiological.